Baghdad’s Solar Power Potential: An Exploration Using PVsyst and HelioScope at Al-Khwarizmi College of Engineering - Mahdi, Reem Omar; Hacham, Wisam (Al-Khwarizmi Engineering Journal, 2025)
The energy business has grown explosively over the past few decades because of increased global energy consumption, which has had catastrophic effects on the environment. As a result, the entire planet has begun transitioning to green energy generation, which has zero negative effects on the natural world. Solar electricity has the highest efficiency amongst all forms of renewable energy. This study examines the monthly grid performance of a hypothetical 100 MWp solar facility linked to the Al-Khwarizmi College of Engineering system. Meteonorm 8.0 data are utilised in the simulation, which is run in PVsyst 7.2 and HelioScope software. Maximum energy production is the goal of the simulation, which is implemented at a constant tilt angle throughout the year. The building’s latitude is used to set the best angles or an east–west angle that is fixed 10 degrees to the south azimuth. The 3D display in HelioScope allows for a natural, insightful design process, enabling the selection of highly effective design options and the analysis of shading and panel orientation effects. The use of HelioScope and PVsyst software can provide insights into the amount of energy production from solar panels in a specific area. In this work, the amounts of energy generated using PVsyst and HelioScope are 1,500.303 and 849.7653 MWh/year, respectively.